Manusia Bijaksana Menurut Taoisme - Pitoyo, Joko (Jurnal Filsafat "WISDOM", 2017)
Tao’s view about reality is monistic: the universe comes from Tao, is absorbed by Tao, and ultimatelly united in Tao. Tao is thebasic principle of reality. Everything exiss naturally,spontaneously, without planning, without willing. Human beingsexist from Tao and get Te from Tao. They are not superior to otherbeings. All beings are principally equal difference is justfunctionally. Like other beings, human being are part of theuniverse. The their prudence man tries always in harmony with theunivers so as to unite to it. He tries to live narurally. Everythingflows in accordance with pure nature as expression of  Te  to comeback to Tao again. Tao calls human beings to come back to nature,to become human.